Engineering students: between empowerment and gender binarism - Moraes, Adriana Zomer de (2018)
This article, based on interviews with ninth semester engineering students (2014), deals with their academic experiences and conceptions of gender in the professional field. The dialectical and historical materialism, as a reference, aims to establish connections between the private and the social totality and between subjectivity and objectivity in the historical process of transformations and permanence. The increase in the number of admissions of women in engineering programs demands a continuous confrontation of female students who express empowerment strategies paradoxically accompanied by attributes supported by gender binarism. In turn, colleagues and teachers tend to reinforce the sexual division of work in new ways.